2023
DOI: 10.1103/physrevb.107.054107
|View full text |Cite
|
Sign up to set email alerts
|

Light: A new handle to control the structure of cesium lead iodide

Abstract: CsPbI3 is of high interest for photovoltaic applications owing to its low bandgap, provided it could be stabilized in its γ perovskite phase. Instead, it energetically prefers to adopt a so-called yellow, δ phase, with much larger bandgap and reduced photovoltaic properties. Here, using an original constrained Density Functional Theory method, we mimic the effect of thermalized photoexcited carriers, and show that larger concentrations in photo-excited carriers (i.e. larger optical pump fluences) effectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
0
1
Order By: Relevance
“…This behavior is understandable since the polar distortion (polarization) primarily occurs along the c direction, while the reduction in volume under light illumination is alleviated by the expansion of a and b . Remarkably, the magnitude of the relative lattice strain observed in MoBr 2 O 2 is much greater than that observed in BaTiO 3 and PbTiO 3 , , due to the large coupling between polar distortion and lattice strain; see Figure S10. It is noteworthy that all three lattice constants of MoCl 2 O 2 undergo a contraction upon light illumination, which starkly contrasts with the behavior observed in other compounds examined in this study and reported in previous works. , This unusual phenomenon is presumably because of a negative thermal expansion with increasing temperature in MoCl 2 O 2 .…”
Section: Resultscontrasting
confidence: 99%
“…This behavior is understandable since the polar distortion (polarization) primarily occurs along the c direction, while the reduction in volume under light illumination is alleviated by the expansion of a and b . Remarkably, the magnitude of the relative lattice strain observed in MoBr 2 O 2 is much greater than that observed in BaTiO 3 and PbTiO 3 , , due to the large coupling between polar distortion and lattice strain; see Figure S10. It is noteworthy that all three lattice constants of MoCl 2 O 2 undergo a contraction upon light illumination, which starkly contrasts with the behavior observed in other compounds examined in this study and reported in previous works. , This unusual phenomenon is presumably because of a negative thermal expansion with increasing temperature in MoCl 2 O 2 .…”
Section: Resultscontrasting
confidence: 99%